Identification of pest insects, predators and phytopathogenic fungi of Cucurbita moschata (Cucurbitaceae) “loche” - Esquen-Bayona, Damaris; Facultad de Ciencias Biológicas, Universidad Nacional Pedro Ruiz Gallo, Calle Juan XXIII, Lambayeque (2021)
Objective: Identification of pest insects, predators and phytopathogenic fungi of the “loche” Cucurbita moschata Duch (Cucurbitaceae) crop in Ucupe, Mocupe-Lambayeque. Methods: random sampling, five sampling points were taken per crop. Results: Bemisia tabaci attacks the milk crop, it was found causing scratches on the underside of the leaves. Thrips tabaci is a pest that locates on the youngest shoots. Diaphania nitidalis, this is the pest that causes the most damage, since it is a borer insect that attacks fruit, stems, and flowers. Among the controllers: Chrysoperla externa, Rhinacloa sp., Neides sp., Orius sp. and Cicloneda sanguinea. Among the phytopathogenic fungi found Cunninghamella spp., Colletotrichium sp., Memnoniella sp., Verticillium sp., Cladosporium sp. and Stemphylium sp.